Physical Characteristics Underpinning Lunging and Change of Direction Speed in Fencing. Issue 8 (August 2016) - Turner, Anthony; Bishop, Chris; Chavda, Shyam; Edwards, Mike; Brazier, Jon; Kilduff, Liam P.
Abstract : Abstract: Turner, A, Bishop, C, Chavda, S, Edwards, M, Brazier, J, Kilduff, LP. Physical characteristics underpinning lunging and change of direction speed in fencing. J Strength Cond Res 30(8): 2235–2241, 2016—Lunge velocity (LV) and change of direction speed (CODS) are considered fundamental to success during fencing competitions; investigating the physical characteristics that underpin these is the aim of this study. Seventy fencers from the British Fencing National Academy took part and on average (± SD ) were 16.83 ± 1.72 years of age, 178.13 ± 8.91 cm tall, 68.20 ± 9.64 kg in mass, and had 6.25 ± 2.23 years fencing experience. The relationship between anthropometric characteristics (height, arm span, and adductor flexibility) and measures of lower-body power (bilateral and unilateral countermovement jump height and reactive strength index) were examined in their ability to influence LV and CODS. In testing the former, fencers lunged (over a self-selected distance) to and from a force plate, where front leg impact and rear leg propulsive force were quantified; the lunging distance was divided by time to establish LV. Change of direction speed was measured over 12 m involving shuttles of between 2 and 4 m. Results revealed that LV and CODS averaged at 3.35 m·s −1 and 5.45 seconds, respectively, and in both cases, standing broad jump was the strongest predictor ( r = 0.51 and −0.65, respectively) of performance. Rear leg drive and front leg impact force averaged at 14.61 N·kg −1 and 3 times body weight, respectively, with single leg jumps revealing an asymmetry favoring the front leg of 9 ± 8%. In conclusion, fencers should train lower-body power emphasizing horizontal displacement, noting that this seems to offset any advantage one would expect fencers of a taller stature to have. Also, the commonly reported asymmetry between legs is apparent from adolescence and thus also requires some attention.